Answer:
x = 25/3
Step-by-step explanation:
2x-5=20-x
2x-5+5=x+20+5 (add 5 both to both sides)
2x = -x + 25
2x + x = -x + x + 25 (add x to both sides)
3x = 25
3x/3 = 25/3 (divide both sides by 3)
x = 25/3
Answer with explanation:
A Rule which expresses that for every input, the output is an even number can be written in many ways
f(x)=2 x , where x is any Integer.
f(n)=4n, where n is any Integer.
f(s)=6s, where s is any Integer.
f(k)=8k, where k is any Integer.
----------------------
There can be many more expressions.
In these expressions,if you replace,x ,n,s and ,k by any integer , the result will be an Even Number(Positive Even Number or Negative Even Number).